Interpersonal Relationships in the Contemporary 21st Century Society - Ferreira, J. (2025)
Interpersonal relationships in contemporary society in the 21st century Over the last twenty years, we have witnessed a social transformation in global society, with implications for our way of life and social and human relationships. This is a problem and a shared responsibility for everyone, including citizens, political decision-makers and academic thinkers. We are witnessing the evolution of a more individual and less collective society, but one that upholds democratic values and ethical principles for an inclusive society. We are in an accelerated process of digital transition and today the daily reality of every citizen is to deal with 60% of their daily social issues through digital platforms, including social media. Verbal and human communication is being replaced by digital communication based on language codes, with negative consequences for social and human relations. Interpersonal relations are reflected in the relationship of social solidarity in contemporary society, particularly at the intergenerational level. The changes we observe in social reality can be explained by the virtualisation of human rights, ethical principles and values of coexistence in society, and can be explained by contexts of vulnerability, uncertainty, social precariousness, armed conflicts, as well as by economic orientations towards rapid wealth accumulation and the formation of new social, economic and political elites.